Breaking with the Principles of Coreduction to Form Stoichiometric Intermetallic PdCu Nanoparticles. Issue 6 (23rd April 2022) - Mathiesen, Jette K.; Bøjesen, Espen D.; Pedersen, Jack K.; Kjær, Emil T. S.; Juelsholt, Mikkel; Cooper, Susan; Quinson, Jonathan; Anker, Andy S.; Cutts, Geoff; Keeble, Dean S.; Thomsen, Maria S.; Rossmeisl, Jan; et al.
Abstract: Intermetallic nanoparticles (NPs) have shown enhanced catalytic properties as compared to their disordered alloy counterparts. To advance their use in green energy, it is crucial to understand what controls the formation of intermetallic NPs over alloy structures. By carefully selecting the additives used in NP synthesis, it is here shown that monodisperse, intermetallic PdCu NPs can be synthesized in a controllable manner. Introducing the additives iron(III) chloride and ascorbic acid, both morphological and structural control can be achieved. Combined, these additives provide a synergetic effect resulting in precursor reduction and defect‐free growth; ultimately leading to monodisperse, single‐crystalline, intermetallic PdCu NPs. Using in situ X‐ray total scattering, a hitherto unknown transformation pathway is reported that diverges from the commonly reported coreduction disorder–order transformation. A Cu‐rich structure initially forms, which upon the incorporation of Pd(0) and atomic ordering forms intermetallic PdCu NPs. These findings underpin that formation of stoichiometric intermetallic NPs is not limited by standard reduction potential matching and coreduction mechanisms, but is instead driven by changes in the local chemistry. Ultimately, using the local chemistry as a handle to tune the NP structure might open new opportunities to expand the library of intermetallic NPs by exploiting synthesis by design. Abstract : Using in situ X‐ray total scattering, a new transformation pathway of single‐crystalline intermetallic PdCu nanoparticles is reported. The generality of reported disorder–order routes for stoichiometric intermetallic nanoparticle formation, relying on matching standard reduction potentials of metal ion species, is questioned. Instead, changes in local chemistry are found to be a decisive factor, which opens new avenues for designing catalytic nanoparticles.